Safe and secure classification protocol in two-tiered sensor networks - Rui LI; Jin-guo LI; Hao CHEN (Tongxin xuebao)
A safe and security classification protocol named SSC was proposed for two-tiered sensor networks,which enable storage nodes to process classification correctly without knowing both the value of classifying rules and the data which will be classified.To protect privacy,an oblivious comparison technique was presented.MHash,which enable storage nodes to compare data items from sink and sensors without knowing their values.Based on MHash and prefix membership verification technique,classification target was achieved in protecting the privacy of both sensor collected data and sink issued classification rules.To verify the correctness of classification results,a crossed neighborhood technique was proposed which organize sensors and data items in one sensor in sequences,to allow the sink checking the correctness of sampling classification results.Analysis and experimental results validate the efficacy and efficiency of SSC protocol.